ANTIOXIDANT ACTIVITY OF LEAF EXTRACT FROM SIDA SUBCORDATA SPAN - Rahma Yulia; Dachriyanus Dachriyanus; Amri Bachtiar (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
This Study has tested the antioxidant activity of the extracts from Sida subcordata Span. Testing is done with antioxidant activity using DPPH method provides. Testing of antioxidant activity in vitro with spectrophotometric methods based on absorbance measurements radical DPPH (1,1-diphenylpicrylhydrazyl). All the extracts Showed radical scavenging activity. The ethyl acetate and methanol extracts were the most Appropriate as sources of antioxidant compounds as shown by Reviews their inhibition percentage (IP) values. Percentage inhibitor to extract ethyl acetate and methanol extract respectively 76.16% and 79.28% at a concentration of 1 mg / ml to 0.05 mM DPPH. while the results of the testing activities of antioxidant compounds y pure ethyl acetate extract fraction showed a smaller percentage inhibitor that is equal to 30% at the same concentration. Keyword - Sida subcordata Span, Malvaceae, Antioxidant, Alkaloid